2016
DOI: 10.1103/physrevb.94.020402
|View full text |Cite
|
Sign up to set email alerts
|

Edge instability in a chiral stripe domain under an electric current and skyrmion generation

Abstract: Motivated by the recent experimental observations on the skyrmion creation by cutting chiral stripe domains under a current drive [Jiang et al., Science 349, 283 (2015)], we study the mechanism of skyrmion generation by simulating the dynamics of stripe domains. Our theory for skyrmion generation is based on the fact that there are two half skyrmions attached to the ends of a stripe domain. These half skyrmions move due to the coupling between the skyrmion topological charge and current. As a consequence, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
2
47
1
Order By: Relevance
“…The creation of skyrmion bubbles in such a junction constriction driven by inhomogeneous spin currents was further studied independently by Heinonen et al [106], S.-Z. Lin [107], and Liu et al [108], confirming its efficient mechanism and device compatibility suitable for future applications.…”
Section: Spin-polarized Electric Currentmentioning
confidence: 88%
“…The creation of skyrmion bubbles in such a junction constriction driven by inhomogeneous spin currents was further studied independently by Heinonen et al [106], S.-Z. Lin [107], and Liu et al [108], confirming its efficient mechanism and device compatibility suitable for future applications.…”
Section: Spin-polarized Electric Currentmentioning
confidence: 88%
“…We notice that the current density needed to break the stripe domains is fairly low. 22 This phenomenon indicates that the energy barrier at the vicinity of the magnetic domain transition is lowered by increasing magnetic field 23 and this might be the reason for the reduced current density. It also should be mentioned that the critical magnetic field to form the biskyrmions can be influenced by the sample thickness, which results in the sequence of biskyrmion generation and annihilation along the gradient thickness of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between topological charge and conduction electrons induces the spin Hall torque that generates the observed Néel-type skyrmions. 22 Based on the theoretical simulations, it has been proposed that the current-induced STT can facilitate the generation of the Bloch-type skyrmions. 22 However, thus far, no experimental study on this issue has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of magnetic skyrmions has recently been demonstrated by applying magnetic fields 10 , spin-polarized currents 27,32 , local heating 33 , laser beams 34,35 and electric voltage 36,37 . Meanwhile, skyrmions can also be generated in geometrical constricted devices 6,[38][39][40][41][42] by applying electrical currents 43 . For example, the dynamical generation of skyrmions can be realized by squeezing chiral band domains through a (magnetic) geometrically constriction after being subjected to spatially inhomogeneous spin-orbit torques (SOTs) 6,40,41,44,45 .…”
Section: P a G E 3 | 18mentioning
confidence: 99%
“…Meanwhile, skyrmions can also be generated in geometrical constricted devices 6,[38][39][40][41][42] by applying electrical currents 43 . For example, the dynamical generation of skyrmions can be realized by squeezing chiral band domains through a (magnetic) geometrically constriction after being subjected to spatially inhomogeneous spin-orbit torques (SOTs) 6,40,41,44,45 . In addition, skyrmions can also be generated in a constricted region as a result of inhomogeneous current induced nonlinear magnetization dynamics 38,41 .…”
Section: P a G E 3 | 18mentioning
confidence: 99%